2014
DOI: 10.1103/physreva.90.043815
|View full text |Cite
|
Sign up to set email alerts
|

Light localization induced by a random imaginary refractive index

Abstract: We show the emergence of light localization in arrays of coupled optical waveguides with randomness only in the imaginary part of their permittivity and develop a one-parameter scaling theory for the normalized participation number of the Floquet-Bloch modes. This localization introduces a new length scale in the decay of the autocorrelation function of a paraxial beam propagation. Our results are relevant to a vast family of systems with randomness in the dissipative part of their impedance spatial profile.PA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 37 publications
5
46
0
Order By: Relevance
“…Several non-Hermitian models with disorder or incommensurate potentials have been investigated, in which non-Hermiticity is introduced by considering either complex on-site potentials, phenomenologically describing dissipation and/or amplification with the surrounding enviroment, or asymmetric hopping amplitudes, such as in systems with synthetic imaginary gauge fields. In systems with on-site complex disorder (non-Hermitian Anderson model), it was shown that a purely imaginary disorder can induce localization like in the Hermitian Anderson localization problem, with a duality between dissipation and amplification [21,22,27,30,34]. On the other hand, for real-energy on-site potential disorder a non-Hermitian delocalization transition is observed * stefano.longhi@polimi.it by application of an imaginary gauge field (Hatano-Nelson-Anderson model [23-26, 29, 33, 39, 46, 47, 49]).…”
Section: Introductionmentioning
confidence: 99%
“…Several non-Hermitian models with disorder or incommensurate potentials have been investigated, in which non-Hermiticity is introduced by considering either complex on-site potentials, phenomenologically describing dissipation and/or amplification with the surrounding enviroment, or asymmetric hopping amplitudes, such as in systems with synthetic imaginary gauge fields. In systems with on-site complex disorder (non-Hermitian Anderson model), it was shown that a purely imaginary disorder can induce localization like in the Hermitian Anderson localization problem, with a duality between dissipation and amplification [21,22,27,30,34]. On the other hand, for real-energy on-site potential disorder a non-Hermitian delocalization transition is observed * stefano.longhi@polimi.it by application of an imaginary gauge field (Hatano-Nelson-Anderson model [23-26, 29, 33, 39, 46, 47, 49]).…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, dissipation in ordered lattices have proved to be destructive for the originally ballistic transport. Namely, it evokes the mobility transition towards diffusive light propagation, when introduced homogeneously 27 , and exponential localization, when randomized 28 . Instructively, the dissipation introduced at the boundaries of passive chains (or mimicked by semi-infinite propagating leads) organizes non-trivial transitions in the scaling of relaxation 29 , transparency 30 , and arising asymmetry of wave propagation 31 , depending on the levels of disorder and nonlinearity.…”
mentioning
confidence: 99%
“…We note that the phenomenon we described here relies on providing coherent gain in a cavity, and thus they may also be observed in other non-Hermitian platforms for propagating waves, including acoustics [39,40] and phononics [41], and potentially even electronics [42] and magnonics [43]. Furthermore, we have considered only deterministic systems here, and it remains an open question what the impact of Poynting's threshold is in disordered active structures, especially when the disorder leads to Anderson localization [44].…”
Section: Discussionmentioning
confidence: 88%